“I Don’t Have the Right to Despond Myself”: The Executive’s Work Suffering - Lottermann, Fernanda (2021)
This study analyzes the repercussions of the work experience on the mental health of the executives of the food industry in the region of Vale do Caí, Rio Grande do Sul state, Brazil. With the qualitative design, the survey counted on eight interviewees. We used focused interviews and questionnaires. The data were assessed by the content analysis proposed by Laville and Dionne. The fear of dismissal and the need to abdicate one's subjectivity in favor of the company are factors for suffering. The organization of work is negligent with mental health care and promotes mechanistic ways of being, aggravating the risks to the integrity of workers. Psychology promotes reflections and enables the resignification of the suffering generated by work.